2012
DOI: 10.1093/hmg/dds030
|View full text |Cite
|
Sign up to set email alerts
|

Altered maturation of the primary somatosensory cortex in a mouse model of fragile X syndrome

Abstract: Fragile X syndrome (FXS) is the most common inherited form of intellectual disability and results from the loss of the fragile X mental retardation protein (FMRP). Many fragile X-related cognitive and behavioral features emerge during childhood and are associated with abnormal synaptic and cellular organization of the cerebral cortex. Identifying the roles of FMRP in cortical development will provide a basis for understanding the pathogenesis of the syndrome. However, how the loss of FMRP influences the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
3
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 43 publications
7
85
3
4
Order By: Relevance
“…Furthermore, we found that neurons derived from KO mice produce many nascent synaptic proteins at a higher rate than that of WT mice, many of which are reportedly direct FMRP targets. Given that FMRP expression declines during later brain maturation (38,39), it may be that the age-dependent differences that we observed between WT and KO synaptic proteomes reflect a declining influence of FMRP (in WT) on nascent protein synthesis at the elongation step.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, we found that neurons derived from KO mice produce many nascent synaptic proteins at a higher rate than that of WT mice, many of which are reportedly direct FMRP targets. Given that FMRP expression declines during later brain maturation (38,39), it may be that the age-dependent differences that we observed between WT and KO synaptic proteomes reflect a declining influence of FMRP (in WT) on nascent protein synthesis at the elongation step.…”
Section: Discussionmentioning
confidence: 92%
“…Synaptoneurosomes (SNs) were isolated according to Till et al (2012) with minor modifications, one to four weeks after finishing the tube tournaments. Briefly, the frontal parts of freshly isolated cortices were gently homogenized with a Teflon-glass homogenizer (10 mM HEPES, 2 mM EDTA, 2 mM EGTA, 0.5 mM DTT, protease inhibitors (Roche)).…”
Section: Synaptoneurosome Preparationmentioning
confidence: 99%
“…Neste estudo, a ausência da FMRP causou defeitos de maturação e proliferação neuronal e dismorfismo de espinhas dendríticas, especificamente no córtex cerebral somatosensorial primário (TILL et al, 2012). Embora a maturação neuronal ainda tenha ocorrido no córtex somatosensorial, sua capacidade de formar circuitos sinápticos foi perdida, o que foi atribuído à redução da plasticidade neuronal.…”
Section: A Fmrp E O Córtex Cerebralunclassified
“…Em contraste com nossas observações, Till e colaboradores (TILL et al, 2012) não observaram nenhuma marcação em células da glia. Enquanto a IHQ não permite uma discriminação inequívoca entre células neuronais ou gliais, a maioria das nossas observações ao microscópio em regiões corticais e hipocampais mostrou células com morfologia indicativa de neurônios, enquanto na região do corpo caloso, observamos marcação que é sugestiva de expressão da FMRP e FMRP+12ISO nas fibras de oligodendrócitos (dados não mostrados), que deve ser um achado inespecífico.…”
Section: A Fmrp E O Córtex Cerebralunclassified
See 1 more Smart Citation